Polimorfismo de formas sanguíneas e metaciclogênese in vitro de Trypanosoma cruzi I, II e IV - Piva, Camila (2014)
Trypanosoma cruzi, etiologic agent of American trypanosomiasis or Chagas disease, has broad biological and genetic diversity. Since the late '60s has been recorded an increasing number of outbreaks of infection acquired orally in Brazíl and elsewhere in Latin America. Only in the Brazilian Amazon were described more than 60 outbreaks the acute form of the disease. The aim of this study was to evaluate the impact of the genetic diversity of T. cruzi the polymorphism of blood forma and in vitro metacyclogenesis. For this, 15 strains belonging to discrete typing units (DTUs) T. cruzi l and IV from Amazonas (9strains), and T. cruzi l and ll from Paraná (3), Minas Gerais (2) and São Paulo (1) were used. Variables related to the blood polymorphism were assessed in thin blood smears. The metacyclogenesis was measuredin smear of culture media LIT and M16, stained with Giemsa. The morphological pattern of Tcll strains was consistent with broad forms. In TclV strains predominated slender forms of the parasite, and despite the strain Y is classified as Tcll, she showed morphological characteristics of TclV. However, significant differences related to the polymorphism, were recorded between DTU .Variables of metacyclogenesis differed between the DTUs with descending order of values: Tcll ZTcl ZTclV. The mean number of transitional forms (epimastigote-trypomastigote) and metacyclic trypomastigotes for Tcll was significantly higher, in both LIT and M16medium. Significant difference between Tcl and TclV was observed only in the number of trypomastigotes in LIT .Although there is overlap behavior for the DTU, the general pattern is that different DTU exhibit polymorphism and statistícally metacyclogenesis, suggesting that the genetic diversity of T. cruzi can have a major impact on both the evolution of infection in the mammalian host and in their ability to dispense in nature.